2002
DOI: 10.1021/om010797i
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Heterodinuclear Complexes Formed by Platinum Insertion to Phosphorus-Bridged [1]Ferrocenophane Coordinating to a Metal Fragment

Abstract: A reaction of Pt(PMe3)4 with fcpp (fcpp = 1,1‘-ferrocenediylphenylphosphine) coordinating to CpMn(CO)2 and W(CO)5 fragments gave heterodinuclear complexes (actually they are trinuclear complexes if an iron center of a ferrocene unit is included), in which a Pt(PMe3)2 fragment was inserted into a P−C bond of the fcpp ligand to form P−Pt and η1-C5H4−Pt bonds with a μ-PPhFc bridge (μ-PPhFc = μ-PPh(C5H4FeC5H4)). X-ray analyses showed that the products were Cp(CO)2Mn(μ-PPhFc)Pt(PMe3)2 and (CO)5W(μ-PPhFc)Pt(PMe3)2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…However, 1 shows a rare case of an unsymmetrical bridging l 3 -PR 2 ligand caused by an agostic-like interaction of a P-C sp2 bond with an unsaturated palladium centre. The isolation of complexes with bridging PR 3 ligands is relevant as reaction intermediates in the syntheses of l 2 -PR 2 phosphido derivatives from the corresponding l 2 -PR 3 tertiary phosphine complexes through the oxidative addition of the P-C bond to a metal centre [53][54][55][56][57][58], as well as to rationalize the intramolecular migration of the phosphine ligands. In the same context, the interaction between the P(2)-C(37) bond and the Pd(2) centre in 1 can provide a structural model as intermediates in phosphido transfer processes and even for the syntheses of l 3 -PR phosphinidene derivatives from the corresponding l 2 -PR 2 phosphido complexes.…”
Section: Resultsmentioning
confidence: 99%
“…However, 1 shows a rare case of an unsymmetrical bridging l 3 -PR 2 ligand caused by an agostic-like interaction of a P-C sp2 bond with an unsaturated palladium centre. The isolation of complexes with bridging PR 3 ligands is relevant as reaction intermediates in the syntheses of l 2 -PR 2 phosphido derivatives from the corresponding l 2 -PR 3 tertiary phosphine complexes through the oxidative addition of the P-C bond to a metal centre [53][54][55][56][57][58], as well as to rationalize the intramolecular migration of the phosphine ligands. In the same context, the interaction between the P(2)-C(37) bond and the Pd(2) centre in 1 can provide a structural model as intermediates in phosphido transfer processes and even for the syntheses of l 3 -PR phosphinidene derivatives from the corresponding l 2 -PR 2 phosphido complexes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several research groups and we reported that a low valent transition metal such as a zerovalent platinum complex reacts with a strained phosphaheterocyle coordinating to a metal fragment to give a ring-expanded product with a platinum fragment inserted into a P-C bond [14,15]. Thus, 7 in which 3a is coordinating to a W(CO) 5 fragment was allowed to react with Pt(PPh 3 ) 4 [7].…”
Section: Ring-opening Reactionmentioning
confidence: 98%
“…[105,112] Strained phospha [1]ferrocenophanes 29 can also coordinate through the lone pair on phosphorus to metal fragments (Scheme 4), [113][114][115][116][117] which alternatively may insert into a PÀC bond (Scheme 5). [118,119] Stable phosphonium-bridged [1]ferrocenophanes, sulfurized P V derivatives, and borane adducts of (phenyl)phospha[1]-ferrocenophanes (31) have been prepared and in some cases and subjected successfully to thermal transition-metal-catalyzed ROP. [120,121] Notably, the enthalpies of thermal ROP recorded for (phenyl)phospha [1]ferrocenophane (29, R = Ph, À68 AE 5 kJ mol À1 ) [120] and (methylphenyl)phosphonium [1]ferrocenophane (31, R 1 = Ph, R 2 = Me, À61 AE 5 kJ mol À1 ) suggest slightly smaller strain energies than the typical values for dialkylsila [1]ferrocenophanes despite larger average tilt angles, though this is probably a consequence of the presence of the bulky phenyl substituent.…”
Section: Ansa Complexesmentioning
confidence: 99%